Tanggung Kelompok Bersenjata Non Negara Pada Wilayah Konflik Yang Di Kendalikan Dan Pertanggung Jawabannya - Lekatompessy, Ludya Grafilia; Wattimena, Josina Augustina Yvonne; Leatemia, Wilshen (PATTIMURA Law Study Review, 2024)
ABSTRACT: The armed conflict in Syria involves the Syrian government and rebels on behalf of their organized group the Free Syrian Army (FSA). The Syrian Army has attacked most of the rebel areas in Eastern Ghouta. The armed conflict has caused many problems and misery, especially for the civilian population. Starting from suicide bomb attacks, rocket attacks, and firearms attacks, using civilians as human shields to protect themselves from enemy attacks, often blocking or making it difficult for civilians to access humanitarian assistance, such as food, clean water, and medical care, recruiting children under the age of 18 to participate in armed conflict, and have committed gross violations of human rights, such as murder, torture, rape, and forced displacement of civilians. The research method used in analyzing and discussing the problem is normative, this research is focused on the purpose of examining and knowing the position of non-state armed groups in non-international armed conflicts in controlled areas and non-state groups can be held accountable when not meeting the basic needs of the civilian population in controlled areas. The results of the study state that the position of non-state armed groups in conflict is based on Additional Protocol II to the 1949 Geneva Convention Article 1 paragraph 1. Also in the regulation of humanitarian law contains guarantees of the rights of everyone in the conflict area and limits the power of warring parties not to take actions that are beyond the bounds of humanity. And non-state armed groups that are in conflict can be held accountable for the civilian population, when they do not meet the basic needs of the civilian population in controlled areas. Because the UN Security Council considers that non-state actors have international obligations under international law. If they do not meet the basic needs of the civilian population, they can be responsible for human rights violations and crimes against humanity to protect the civilian population in the area.